Hüsameddin Bidlisi ve “Müntehab-ı Şerh-İ Gülşen-i Raz” isimli eserin tahkik ve tahlili - Şengül, İpek (My University, 2018)
Köklü bir geçmişe sahip olan tasavvuf ilminin ilk kaynakları Arapça kaleme alınmıştır. Daha sonra Ebû Saîd-i Ebu‟l-Hayr, Baba Tâhir-i Uryân, Hücvîrî, Senâî, Ferîdüddin Attâr, Mevlânâ Celâleddin-i Rûmî, Fahreddin Irâkî, Mahmud Şebüsterî, Molla Câmî gibi müelliflerin bazı eserlerini Farsça kaleme almaları ile Farsça tasavvuf dili haline gelmiştir. Tasavvuf dünyasında büyük ün kazanmış ve âdeta bir ders kitabı haline gelmiş olan Gülşen-i Râz adlı eser Mahmud Şebüsterî tarafından kaleme alınmış, pek çok defa ve farklı dillerde şerh ve tercüme edilmiştir. Bu çalışmanın konusu da Hüsâmeddin Bidlîsî tarafından Farsça yazılan Şerh-i Gülşen-i Râz‟dan seçmeler olan müellifi meçhul Müntehab-ı Şerh-i Gülşen-i Râz‟dır. Üç bölüm ve bir ekten müteşekkil olan çalışmamızın birinci bölümünde Gülşen-i Râz‟ın müellifi Mahmud Şebüsterî ve Gülşen-i Râz şerhleri, ikinci bölümünde Hüsâmeddin Bidlîsî‟nin hayatı ve eserleri, üçüncü bölümünde Hüsâmeddin Bidlîsî‟nin Şerh-i Gülşen-i Râz‟ı ve Müntehab-ı Şerh-i Gülşen-i Râz adlı eser incelenmiş olup ekte tenkitli metin neşri olarak Müntehab-ı Şerh-i Gülşen-i Râz‟ın Farsça metnine yer verilmiştir.Bu çalışma ile akademi dünyasına küçük de olsa bir katkı sağlanmış olması hedeflenmektedir.

The earliest sources of Sufi knowledge, which has a long history, are Arabic. Later with some works of the authors, who wrote some of his works in Persian such as Ebû Saîd-i Ebu‟l-Hayr, Baba Tâhir-i Uryân, Hücvîrî, Senâî, Ferîdüddin Attâr, Mevlânâ Celâleddin-i Rûmî, Fahreddin Irâkî, Mahmud Şebüsterî, Molla Câmi, Persian has become a mystic language. Gülşen-i Râz, which has gained a great reputation in the world of Sufism and has become a course book, has been received by Mahmud Sebüsterî and commented and translated many times and in different languages. The subject of this study is Müntehab-i Sharh-i Gülşen-i Râz, an election from Sharh-i Gülşen-i Râz, written in Persian by unknow author. In the first part of our work which consists of three parts and one additional part, Mahmud Şebüsterî who is writer of Gülşen-i Râz and Gülşen-i Râz‟s annotations, in the second part Hüsâmeddin Bidlîsî's life and works and in the third part Hüsâmeddin Bidlîsî's Şerh-i Gülşen-i Râz and Müntehab-i Sharh-i Gülşen-i Râz were examined and the criticized Persian text of Müntehab-i Şerh-i Gülşen-i Râz was included in the text of the additional text.It is aimed that a small contribution is made to the world of academia with this study.
Keywords: Gulshan i Raz; Gülşen-i Râz; Hüsameddin Bidlisi; Hüsâmeddin Bidlîsî; Islam; İslam; Müntehab; Müntehab Shabestari; Sharh; Şebüsterî; Şerh